ANALISIS RISIKO INVESTASI TERHADAP RETURN SAHAM TAHUNAN PADA INDUSTRI TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hikma Niar (AkMen JURNAL ILMIAH, 2015)
This study aimed to determine the impact of investment risk on stock returns in the telecommunications industry Go-public listed in the Stock Exchange in 2008-2013, viewed from the aspect of investment risk in unison and the impact on stock returns in the telecommunications industry Go-public listed in the Stock Exchange years 2008-2013, in terms of partial aspects. The research method used is multiple regression analysis. Results from this study is that expected return variables, market risk / beta market, business risk and financial risk, simultaneously (together) have a significant effect on stock returns for the telecommunications industry Go-public listed in the Stock Exchange in 2008-2013. This is evidenced by the results of the F test, simultaneously independent variables affect the dependent variable with significance levels below 0.05 and F test results in this study indicate the significance level of 0.000. Partially (separately), variable expected return, market risk / beta market, and business risk, significant effect on stock returns, while the financial risk variables had no effect on stock returns for the telecommunications industry Go-public listed in the Stock Exchange in 2008- 2013. This is evidenced by the results of the t test, partially independent variables each affect the dependent variable with significance level below 0.05, and of the four variables have a significance level respectively 0.000, 0.031, 0.000, and 0.184.